PENGEMBANGAN BAHAN AJAR MATERI POLA BILANGAN MENGGUNAKAN PENDEKATAN SAINTIFIK BERBANTUAN ICT UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP PADA SISWA MTs KELAS VIII - Nanang Abdul Salam; Luvy Syliana Zanthy; Heris Hendriana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This development research is motivated because students need practical teaching materials when studied in the classroom and outside the classroom. This study aims to develop teaching materials for number patterns using a scientific approach assisted by ICT to improve students' conceptual understanding skills. This research is a type of R&D (Research and Development) research with the procedure for developing teaching materials using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were private MTs students in Cianjur with data analysis techniques using qualitative and quantitative descriptive. The data that has been collected is then analyzed using Microsoft Excel. Student responses to teaching materials are included in the good category with an achievement percentage of 72,86%, meaning that student responses to learning with teaching materials using number pattern materials using an ICT-assisted scientific approach received a good response. The results of the t-test got the results tcount = 29,65 > ttable = 1,696, meaning that the students' ability to understand mathematical concepts increased after using number pattern teaching materials using a scientific approach assisted by ICT.